The design, synthesis, antioxidant, and antihypoxia activities of two new hydroxydaidzein derivatives. Issue 5 (October 2022) - Da, Qingyue; Shao, Jin; Zhang, Pengpeng; Zhang, Jie; Ma, Huiping; Jing, Linlin
7, 8, 3', 4', 5'-Pentahydroxyisoflavone (8, 3', 5'-trihydroxydaidzein) and 6, 7, 8, 3', 4', 5'-hexahydroxyisoflavone (6, 8, 3', 5'-tetrahydroxydaidzein) are synthesized via a simple and effective method using commercially available daidzein as a raw material. Their structures are confirmed using spectroscopic analyses (infrared, nuclear magnetic resonance, and mass spectrometry), and their purities are determined by high-performance liquid chromatography. The antioxidant capacities are investigated by utilizing 1, 1-diphenyl-2-picryl-hydrazyl radical scavenging, superoxide radical scavenging, nitric oxide radical scavenging, reducing power, and phosphomolybdenum assays. The antihypoxia activity is examined using a hypoxia-induced PC12 cell injury model. The antioxidant and antihypoxia abilities of 8, 3', 5'-trihydroxydaidzein and 6, 8, 3', 5'-tetrahydroxydaidzein are greatly improved in comparison with daidzein. These results indicate that 8, 3', 5'-trihydroxydaidzein and 6, 8, 3', 5'-tetrahydroxydaidzein are excellent antioxidant agents and can be used for alleviating injury induced by hypoxia.